ANALISIS SISTEM DISTRIBUSI PRODUK BEKU MI, AYAM PENYET DAN BAKSO PADA PT DEF DI OUTLET WILAYAH SURABAYA - Ika Khairunisa Salshabila; Lilis Sulandari; Qorry’ Aina; Aisyah Nurin Kamiliya (CV. KAMPUS AKADEMIK PUBLISING, 2026)
The cold chain distribution system plays a crucial role in maintaining the quality and safety of frozen food products. This study aims to analyze the distribution system for frozen noodles (mi), fried chicken (ayam penyet), and meatballs (bakso) at PT DEF in outlets across the Surabaya region, covering the stages of preparation, transportation, and product receipt. A qualitative descriptive method was employed through direct observation, structured interviews with the warehouse manager, warehouse staff, quality control personnel, and drivers, as well as documentation of standard operating procedures, temperature logs, and distribution data. The results indicate that at the product handling stage, storage in cold storage maintains a stable temperature of -18°C to -22°C. During transportation, refrigerated vehicles equipped with a Thermo King cooling system were used, although field findings revealed a malfunction in the vehicle temperature indicator. The distribution chain concludes with visual quality and quantity inspections upon receipt at outlets. External constraints such as traffic congestion still have the potential to affect temperature stability during distribution. Overall, the frozen product distribution system at PT DEF has been quite effective in maintaining product quality through the implementation of a cold chain system.